1976
DOI: 10.1080/00288330.1976.9515611
|View full text |Cite
|
Sign up to set email alerts
|

Identification and classification of the aettological agents of primary amebic meningo‐Encephalitis

Abstract: The history of pathogenic "free-living" amebae is briefly reviewed. An appraisal of methods of identification is made, and of a range of practicable methods is presented. The three current classification schemes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Many authors (Carter 1970;Culbertson 1971;Chang 1974;Cursons & Brown 1976;Cerva 1978) have reported that N. fowleri is extremely sensitive to 0.5-1.0% NaCl. Besides the chemical composition of the waters, both temperature and pH also affect the distribution of these amoebae; Stevens et al (1977) recorded a temperature range of 35-38°C, for the isolation of N. fowleri from thermally polluted lakes, and Wellings et al (1977) recorded a range of 16-34.5°C.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many authors (Carter 1970;Culbertson 1971;Chang 1974;Cursons & Brown 1976;Cerva 1978) have reported that N. fowleri is extremely sensitive to 0.5-1.0% NaCl. Besides the chemical composition of the waters, both temperature and pH also affect the distribution of these amoebae; Stevens et al (1977) recorded a temperature range of 35-38°C, for the isolation of N. fowleri from thermally polluted lakes, and Wellings et al (1977) recorded a range of 16-34.5°C.…”
Section: Discussionmentioning
confidence: 99%
“…Situated south of Rotorua in Taupo, this pool was chosen as it was the site of the 1974 fatal case of PAM in New Zealand (Cursons & Brown 1976). This is also a natural thermal pool, the hot water source being a thermal spring.…”
Section: Otumuheke Streammentioning
confidence: 99%
See 3 more Smart Citations